IMPLEMENTATION OF JOHNSON'S SHORTEST PATH ALGORITHM FOR ROUTE DISCOVERY MECHANISM ON SOFTWARE DEFINED NETWORK - Akbar Pandu Segara; Royyana Muslim Ijtihadie; Tohari Ahmad (JUTI: Jurnal Ilmiah Teknologi Informasi, 2021)
Software Defined Network is a network architecture with a new paradigm which consists of a control plane that is placed separately from the data plane. All forms of computer network behavior are controlled by the control plane. Meanwhile the data plane consisting of a router or switch becomes a device for packet forwarding. With a centralized control plane model, SDN is very vulnerable to congestion because of the one-to-many communication model. There are several mechanisms for congestion control on SDNs, one of which is modifying packets by reducing the size of packets sent. But this is considered less effective because the time required will be longer because the number of packets sent is less. This requires that network administrators must be able to configure a network with certain routing protocols and algorithms. Johnson's algorithm is used in determining the route for packet forwarding, with the nature of the all-pair shortest path that can be applied to SDN to determine through which route the packet will be forwarded by comparing all nodes that are on the network. The results of the Johnson algorithm's latency and throughput with the comparison algorithm show good results and the comparison of the Johnson algorithm's trial results is still superior. The response time results of the Johnson algorithm when first performing a route search are faster than the conventional OSPF algorithm due to the characteristics of the all pair shortest path algorithm which determines the shortest route by comparing all pairs of nodes on the network.